CONFIGURATION OF A FLAT ROOF SOLAR POWER PLANT FOR MAXIMUM ELECTRICITY PRODUCTION - Hadžiselimović, Neja (Journal of Energy Technology, 2025)
Commercial solar power plants are often installed on larger industrial, warehouse and commercial buildings. Modern prefabricated constructions of such buildings dictate architectural solutions involving flat roofs, which are particularly suitable for the installation of larger solar power plants. This research investigates which configuration of solar module installation and which inclinations are suitable for implementation on a flat roof to achieve maximum annual electricity production. It aims to determine the maximum annual production per unit area and per installed power of the solar modules. The simulation results are conducted for all months of the year, and for the geographic latitude and longitude of the town of Lenart in Slovenia.